World And Uzbek Experience in Distance Education - Islamova Maftuna Sharofiddinovna (Genius Journals, 2022)
This article examines the emergence of the distance education system of the XXI century, the world experience of distance education, the advantages and disadvantages of distance education, the use of distance education in higher and secondary education, the prospects of distance education in Uzbekistan in 2019-2020 and general conclusions on distance education
Keywords: Distance learning; distance; learning; distance learning